Pemilihan Bahasa yang Tepat: Kunci Sukses dalam Menyampaikan Pesan - Siti Koriah; Sugiarti Sugiarti; Tika Safitri (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to identify various factors that influence language choice in communication, as well as to analyze how the use of appropriate language can have a positive impact on the success of message delivery. The method used is qualitative research with a descriptive approach. Data were collected through documentation techniques and analyzed using thematic methods. The results of the study indicate that success in delivering messages is greatly influenced by language choice, which depends on a number of factors, such as communication context, communication objectives, audience background and characteristics, media or communication channels, and relationships between speakers. The selection of appropriate language has been shown to improve message clarity, build emotional connections, strengthen the credibility of the communicator, avoid misunderstandings, and increase the appeal and memorability of the message. These findings emphasize the importance of choosing the right language in the communication process so that messages can be delivered effectively and easily understood as they should.